Analysis of occupational hazards among workers in the construction industry of Harare, Zimbabwe - Jerie, Steven (Midlands State University, 2015)
The aim of this study was to determine the work-related diseases occurring among workers in the construction sector of Harare. The study also assessed the distribution of occupational injuries and common risk factors of these injuries among workers in the construction industry. A detailed descriptive study was undertaken in the construction industries of Harare with a focus on workers employed in the Southerton industrial area (Harare has 67% of the share of the construction industry in Zimbabwe) between February and April 2012. The occupational hazards among construction workers in Harare vary from the very minor spells of aches and pains to severe and even potentially fatal disorders. Major occupational health problems include musculoskeletal disorders, hearing loss, vibration and, contact dermatitis. These problems are preventable through pretesting equipment, products and processes and exposure monitoring and risk assessment are an essential component of occupational health and safety programmes. Occupational health programmes need to be an integral part of the general safety and health approach and medical surveillance is essential to ensure the fitness of workers as well as their suitability for certain construction jobs. Education and training for the construction workers would assist by giving detailed descriptions of safe work practices.